An Experimental Investigation on Spot Weld Growth on Dissimilar Joints of 304L Austenitic Stainless Steel and Medium Carbon Steel (Part 1) - Nachimani Charde (Institute of Advanced Engineering and Science, 2013)
Carbon steels and stainless steels are more frequently welded joints than any other materials because of their weldability characteristics. So the spot welded joining characteristic of these two materials are discussed in this paper. The experiment was conducted on medium carbon steel and 304L austenitic stainless by varying the process controlling parameters; such as welding current, welding time and electrode pressing force. As such two sets of data were collected to characterize the formation of spot weld using pneumatic based 75kVA spot welder. The first set was made for the variation of welding time and current whereas the second was made for the variation of welding current and electrode force. The welded specimens are finally underwent the tensile test, hardness test and metallurgical test to characterize the weld growth. The weld nugget growth was noticed for the welding current and weld time increment except the electrode force. By increasing the electrode force, the process resistances were reduced and consequently the weld nugget was reduced. Moreover the effect of heat imbalance was clearly noticed in the weld nuggets due to different electrical and chemical properties.